Comparison of Two Entry Methods for Laparoscopic Port Entry: Technical Point of View. (13th June 2012) - Toro, Adriana; Mannino, Maurizio; Cappello, Giovanni; Di Stefano, Andrea; Di Carlo, Isidoro
Abstract : Laparoscopic entry is a blind procedure and it often represents a problem for all the related complications. In the last three decades, rapid advances in laparoscopic surgery have made it an invaluable part of general surgery, but there remains no clear consensus on an optimal method of entry into the peritoneal cavity. The aim of this paper is to focus on the evolution of two used methods of entry into the peritoneal cavity in laparoscopic surgery.